2018
DOI: 10.3390/s18072101
|View full text |Cite
|
Sign up to set email alerts
|

Smart Optical Catheters for Epidurals

Abstract: Placing the needle inside the epidural space for locoregional anesthesia is a challenging procedure, which even today is left to the expertise of the operator. Recently, we have demonstrated that the use of optically sensorized needles significantly improves the effectiveness of this procedure. Here, we propose an optimized configuration, where the optical fiber strain sensor is directly integrated inside the epidural catheter. The new design allows the solving of the biocompatibility issues and increases the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…The system was tested with real tissue [176], providing a preliminary indication of the potential of this technique to localise the epidural space. Some related works can be found in [177,178]. Finally, a multiparameter measurement FBG-based needle is proposed in [179].…”
Section: Fibre Bragg Gratingsmentioning
confidence: 99%
“…The system was tested with real tissue [176], providing a preliminary indication of the potential of this technique to localise the epidural space. Some related works can be found in [177,178]. Finally, a multiparameter measurement FBG-based needle is proposed in [179].…”
Section: Fibre Bragg Gratingsmentioning
confidence: 99%
“…In recent years, the availability of low-cost miniaturized sensors has progressively allowed the realization of smart surgical instruments and needles [ 1 ] that combine the detection of biophysical parameters with therapeutic functions such as the delivery of anesthetic fluid [ 2 ], radiating a surrounding tissue with focused electromagnetic waves to deliver cancer therapies [ 3 ], or performing diagnostic tasks through endoscopic and photoacoustic imaging [ 4 ]. Multifunctional surgical devices benefit from having advanced and miniaturized on-board sensors that can either perform or contribute to diagnostic tasks or provide in situ detection of additional parameters to improve efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide quantitative and sensory based assistance to epidural anesthesia, methods based on Fiber Bragg Gratings (FBGs) have been proposed. Carotenuto et al reported [ 13 ] and tested [ 2 ] a method based on an FBG mounted inside the needle that converts the tip force into a detectable strain. Similar work was recently proposed by De Tommasi et al [ 14 ] using a single FBG assembled in the epidural needle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se realizó una prueba de calibración variando la temperatura para cada índice de refracción de Una de las estructuras más utilizadas para generar LMRs es la fibra en forma de D (D-Shaped fiber) en transmisión [32], [33]. Esta configuración no es tan fácil de manejar como una fibra en la configuración de reflexión, la que se puede utilizar como catéter [67], sonda nasogástrica [68] o incluso para mapeo químico de superficies [69]. Por el contrario, esta versatilidad se convierte en un inconveniente cuando el espesor del thin film a lo largo de la fibra no es uniforme, lo que puede ocurrir debido a la distancia e inclinación con la que se coloca la muestra dentro de la máquina de sputtering, o a los parámetros utilizados para rotar la plataforma donde se coloca la muestra en [70]- [72].…”
Section: Calibración Del Sensorunclassified